PENGARUH KOMPENSASI DAN BEBAN KERJA TERHADAP LOYALITAS KARYAWAN PADA SHOPEE EXPRESS MPUNDA KOTA BIMA - Jaenab, Jaenab; Hidayati, Mawar (Sekolah Tinggi Keguruan dan Ilmu Pendidikan (STKIP) Bima, 2024)
The research aims to determine how compensation and workload have a significant effect on employee loyalty at Shopee Express Mpunda, Bima City so that it can provide input to the leadership at Shopee Express Mpunda, Bima City. This research is quantitative research and the type of research is associative with the population in this research being all employees of Shopee Express Mpunda Kota Bima, so the sampling technique is a saturated sample of 56 respondents while the data collection technique uses observation, literature study and questionnaires, referring to the Likert scale. 5 points were then distributed to 56 respondents. The analytical method used in this research is multiple linear regression which is then analyzed using SPSS version 21 for Windows. The results of this research are that: 1) Compensation has a significant influence on Loyalty to Shopee Express Mpunda Bima City. 2) Workload There is no significant influence on Loyalty to Shopee Express Mpunda Bima City. 3). Compensation and workload have a significant influence on employee loyalty at Shopee Express Mpunda Bima City